How Do Foreign Traders Affect Stock‐Pricing Efficiency? Microstructure‐based Evidence from Korea. (31st July 2021) - Bae, Kyounghun; Eom, Chanyoung; Kim, Younghee
Abstract: We analyze how foreign ownership relates to the short‐term pricing efficiency of common stocks listed on the Korea Stock Exchange. We find that stocks with greater foreign holdings are priced less efficiently. This result is robust to different efficiency measures, estimation methods, and reverse causality concerns. Our evidence suggests that foreign trading deters price corrections, at least in the short term, and thus, has a negative effect on utilitarian traders. Our findings in relation to potential losses provide new insights into the downside risk of financial liberalization at the market microstructure level.